POTENSI ANTIOKSIDAN EKSTRAK ETANOL KULIT BUAH MUNDAR (GARCINIA FORBESII KING.) DENGAN PARAMETER SENYAWA MARKER - Rizki, Muhammad Ikhwan; Triyasmono, Liling; Sari, Anna Khumaira; Dewi, Anita Ratna (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2023)
Mundar plants are native to Kalimantan which are believed to contain various marker compounds that have biological effects. Phenol and tannin are marker compounds found in the skin of G. forbesii fruit which are believed to act as antioxidants. This research aims to determine the antioxidant potential of marker compounds, namely phenol and tannin, by determining the total phenol and total tannin levels in the ethanol extract of G. forbesii fruit peel. Mundar fruit skin was extracted with ethanol solvent then the total phenol content was determined using the Folin-Ciocelteau method using a gallic acid standard and total tannin was determined using the vanillin method using catechin as a standard solution. The test results showed that the phenol content of the ethanol extract of G. forbesii fruit peel was 1.507 ± 0.041 % w/w equivalent to gallic acid and the total tannin was 0.257 ± 0.004 % w/w equivalent to catechin. These results indicate that the ethanol extract of mundar fruit peel has the potential to act as an antioxidant.